Barriers in Proper Maternal Referral Systems: A Scoping Review of Qualitative Research - Dedeh Supriyatin; Khusnul Khotimah; Qorinah Estiningtyas Sakilah Adnani; Bibek Giri (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
The maternal referral system is a crucial component of healthcare services designed to ensure the welfare of women and babies throughout pregnancy, delivery, and the postpartum phase. This method allows pregnant women with complications to get improved and specialized healthcare treatments in adequately equipped and skilled maternity facilities. However, the effectiveness of maternal referral systems is sometimes hindered by several complex and interrelated concerns, especially in resource-limited countries. This research seeks to examine barriers in the maternal referral system. This study utilizes a scoping review of qualitative research techniques to analyze the PEO framework. The P (Population) component examines the attributes of pregnant women and healthcare professionals engaged in the maternal referral system. The E (Exposure) component examines the obstacles faced in the referral process. Finally, the O (Outcome) component examines the impact of these constraints on the quality and accessibility of maternal health care. This scoping review employs many databases, including PubMed, ScienceDirect, Scopus, Springer, and Google Scholar, to identify papers using the phrases